Simultaneous Search with Heterogeneous Firms and Ex Post Competition - Pieter A. Gautier; Ronald P. Wolthoff (Tinbergen Institute, 2006)
In this paper we study the allocation of workers over high and low productivity firms in a labor market with coordination frictions. Specifically, we consider a search model where workers can apply to high and or low productivity firms. Firms that compete for the same candidate can increase their wage offers as often as they like. We show that if workers apply to two jobs, there is a unique symmetric equilibrium where workers mix between sending both applications to the high and sending both to the low productivity sector. But, efficiency requires that they apply to both sectors because a higher matching rate in the high-productivity sector can then be realized with fewer applications (and consequently fewer coordination frictions) if workers always accept the offer of the most productive firm. However, in the market the worker's payoff is determined by how much the firm with the second highest productivity is willing to bid. This is what prevents them from applying to both sectors. For many configurations, the equilibrium outcomes are the same under directed and random search so our results are not driven by random search. We discuss the effects of increasing the number of applications and show that our results can easily be generalized to N-firms.
Keywords: D83; E24; J23; J24; J64; 330; Directed search; multiple applications; efficiency; Suchtheorie; Arbeitsuche; Produktivität; Matching; Wirtschaftsmodell